2018
DOI: 10.1186/s12889-018-6262-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of night eating habits with metabolic syndrome and its components: a longitudinal study

Abstract: BackgroundNight time eating is a risk factor for metabolic syndrome and obesity. The aim of this study was to investigate whether dinner immediately before bed, snacks after dinner, or combinations of both were associated with metabolic syndrome and its components in a large Japanese cohort.MethodsWe enrolled 8153 adults aged 40–54 years who participated in specific medical checkups in an Okayama facility from 2009 to 2010 and from 2013 to 2014. Age-adjusted and multivariable-adjusted odds ratios of metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 37 publications
8
86
1
9
Order By: Relevance
“…Among the various strategies for health promotion, one commonality is the importance of healthy eating habits to prevent obesity [ 2 ]. Several epidemiologic studies have indicated that unhealthy eating habits, such as snacking [ 5 , 6 , 7 , 8 ], eating quickly [ 7 , 9 , 10 ], and eating late-evening meals [ 11 , 12 ], are significantly associated with an increased risk of obesity or central obesity. These previous studies investigated the influence of each eating habit separately, but it is also important to consider the influence of the accumulation of unhealthy eating habits on obesity and central obesity, since unhealthy eating habits tend to overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various strategies for health promotion, one commonality is the importance of healthy eating habits to prevent obesity [ 2 ]. Several epidemiologic studies have indicated that unhealthy eating habits, such as snacking [ 5 , 6 , 7 , 8 ], eating quickly [ 7 , 9 , 10 ], and eating late-evening meals [ 11 , 12 ], are significantly associated with an increased risk of obesity or central obesity. These previous studies investigated the influence of each eating habit separately, but it is also important to consider the influence of the accumulation of unhealthy eating habits on obesity and central obesity, since unhealthy eating habits tend to overlap.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an observational study conducted by Sakurai et al reported that skipping breakfast was closely associated with annual changes in BMI and waist circumference among men [23]. In another longitudinal study, late dinner was associated with obesity [24]. It was uncertain why BMI and WHtR were not increased in people with unhealthy dietary habits in our study; however, it implied that they might not be intermediate factors in our study setting.…”
Section: Discussionmentioning
confidence: 58%
“…Late night eating habits are related to MetS [ 48 ].The present study supported this conclusion by showing that consumption of calories late at night was a risk factor of MetS occurrence. In a preceding study on middle-aged adults without obesity and diabetes, adults consuming more than 48% of daily calories at dinner were reported to have a 1.5 times higher risk of developing MetS [ 49 ].…”
Section: Discussionmentioning
confidence: 99%